New perspectives on career counseling and guidance in Europe Building careers in changing and diverse societies (Springer International Publishing, 2018)
In industrialized societies, individuals are facing major challenges that mobilize many of their psychological and social resources. The world of work is changing constantly. Adults have to adapt their technical skills and knowledge continuously. For teenagers and young adults, choosing a vocation and constructing their future career paths is becoming increasingly difficult. The migration of people and the globalization of the workforce raise questions about social inclusion and the future of affected individuals. These examples highlight of the importance of the field of Career Counseling and Guidance to support citizens individually and collectively in building their future. The challenges our societies face demonstrate how crucial the development of research in this field is. The European Doctoral Programme in Career Guidance and Counselling (ECADOC), funded by the European Commission from 2013-2016, has brought together PhD students working on burning issues in this field, using various theoretical references and methodologies. The four parts of this book present a selection of innovative research aiming to find answers to the named challenges. Part 1 deals with key psychological processes involved in career construction of young adults. Part 2 presents research concerning transitions over the course of life. Part 3 covers research related to interventions of career guidance and counseling. Part 4 outlines perspectives for the future and proposes a European Research Agenda for our field of research. Perspectives on Current Research in Career Guidance and Counseling - Building Careers in Changing and Diverse Societies is dedicated to students, researchers and practitioners in the fields of education, career guidance, psychology, human resource management to inform them about very recent work and promote the development of innovative interventions and programmes.